(untitled) (Journal of actual problems of jurisprudence, 2018)
The article discusses some theoretical and practical problems of applying measures of administrative legal coercion. The author gives a general definition of measures of administrative legal coercion and a description of their individual types. Special attention is paid in the article to measures of administrative legal warning applied in the activities of the internal affairs organs. The main features, goals and objectives of the application of administrative warning measures are highlighted. The organs of internal affairs, in close cooperation with other state bodies, do not easy work in preventing and combating offenses, ensuring public and personal security. In this aspect, a feature of administrative precautionary measures is their goal – not only the prevention of offenses, but also ensuring the rights and freedoms of a person and citizen. The paper draws attention to the diversity of existing administrative precautionary measures, which does not allow the regulatory list of an exhaustive list of measures applied in Kazakhstan. At the same time, such diversity does not preclude the classification of administrative-legal warning measures. The author notes the possibility of various classifications: according to general characteristics, according to objectives, based on the application of certain measures. In this case, the most valuable, from a practical point of view, is the classification by purpose of application. Key words: administrative-legal coercion, measures of administrative warning, administrative-legal prevention, human and civil rights and freedoms.